Continuous homomorphisms of Arens-Michael algebras - Alex Chigogidze (International Journal of Mathematics and Mathematical Sciences)
It is shown that every continuous homomorphism of Arens-Michael algebras can be obtained as the limit of a morphism of certain projective systems consisting of Fréchet algebras. Based on this, we prove that a complemented subalgebra of an uncountable product of Fréchet algebras is topologically isomorphic to the product of Fréchet algebras.